2021
DOI: 10.1590/1414-431x2020e10685
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone I inhibited growth of human chronic myeloid leukemia cells via JNK/ERK mediated apoptotic pathways

Abstract: Tanshinone I (Tan I) is one of the main bioactive ingredients derived from Salvia miltiorrhiza Bunge, which has exhibited antitumor activities toward various human cancer cells. However, its effects and underlying mechanisms on human chronic myeloid leukemia (CML) cells still require further investigation. This study determined the effects and mechanisms of antiproliferative and apoptosis induction activity induced by Tan I against K562 cells. The cytotoxic effect of Tan I at varying concentrations on K562 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…This protein can activate some genes involved in cell proliferation regulation in the MAPK pathway, such as Ras, Raf, ERK, and JNK, to increase proliferation and inhibit apoptosis ( 153 155 ). However, TsIIA not only directly inhibits the expression and phosphorylation of MAPK ( 156 ), but also inhibits the activation and expression of related molecules in its mediated signal pathway, including ERK, JNK, p38 MAPK, etc. ( 157 ).…”
Section: Molecular Mechanism and Target Of Tsiia Anti Hccmentioning
confidence: 99%
See 1 more Smart Citation
“…This protein can activate some genes involved in cell proliferation regulation in the MAPK pathway, such as Ras, Raf, ERK, and JNK, to increase proliferation and inhibit apoptosis ( 153 155 ). However, TsIIA not only directly inhibits the expression and phosphorylation of MAPK ( 156 ), but also inhibits the activation and expression of related molecules in its mediated signal pathway, including ERK, JNK, p38 MAPK, etc. ( 157 ).…”
Section: Molecular Mechanism and Target Of Tsiia Anti Hccmentioning
confidence: 99%
“…The galactose modified PH sensitive Niosomes developed by Hu X et al. can not only target the liver, but also significantly prolong the blood circulation time of TsIIA, and also found that the strength of this ability is positively related to the content of galactose ( 156 ). It is worth mentioning that the existence of mixed micelles also enhances the possibility of developing TsIIA anti liver cancer drugs ( 30 ).…”
Section: Tsiia Targeted Deliverymentioning
confidence: 99%
“…Apoptosis is an autonomous and orderly cell death process controlled by genes that occurs after cells are stimulated by physiological or pathological signals, and tumors have the ability to resist apoptosis via multiple strategies ( Pistritto et al, 2016 ; Huang et al, 2021a ). The antitumor effect of S. miltiorrhiza bioactive compounds has been linked to the induction of apoptosis in multiple studies ( Sun et al, 2021 ). For example, tan IIA induces apoptosis of ovarian cancer A2780 cells by regulating the PI3K/Akt/c-Jun N-terminal kinase (JNK) signaling pathway, which increases the expression of caspase 3, caspase 8, and caspase 9 but decreases the expression of B cell lymphoma 2 (Bcl-2) family proteins (Bcl-w and Bcl-1L) ( Zhang et al, 2019a ).…”
Section: Antitumor Activities Of S Miltiorrhizamentioning
confidence: 99%